Harmonizing Pancasila and Islamic Moderation as a Digital Ethical Framework: A Grounded Strategy of Teacher-Community Synergy - Mukhamad Ainul Yaqin (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
In the era of hyper-connectivity, the massive spread of disinformation and intolerance poses a significant threat to Indonesia’s national cohesion. This study explores how the national ideology, Pancasila, is operationalized into a practical framework for tolerance education by local actors in Lumbang, East Java—a region known for its distinct multicultural harmony. Employing a Grounded Theory approach with in-depth interviews, this research analyzes the synergistic strategies of two key agents: teachers and community leaders. The findings reveal that digital media in this region functions not to create, but to amplify existing social harmony. Teachers act as strategic communicators, applying Inoculation Theory by proactively